Effect of Continuous Lateral Rotation Therapy on Clinical Outcomes in Mechanically Ventilated Critically Ill Adults. - Brito, Anna Luísa A.; Ferreira, Amanda Caroline A.; Costa, Layane Santana P.; F. Silva Júnior, Emanuel Fernandes; Lima Campos, Shirley (Respiratory Care, 2024)
BACKGROUND: This Population, Intervention, Comparison, and Outcomes-guided systematic review assesses continuous lateral rotation therapy versus conventional position changes in mechanically ventilated critically ill adults, evaluating mortality, ICU length of stay (LOS), and hospital LOS as primary outcomes and respiratory function, mechanical ventilation duration, pulmonary complications, and adverse events as secondary outcomes. METHODS: This systematic review follows Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria (International Prospective Register of Systematic Reviews CRD42022384258). Searches spanned databases MEDLINE/PubMed, Embase, Scopus, ScienceDirect, Cochrane, CINAHL, and Web of Science, without language or publication year restrictions. Inclusion criteria involved randomized controlled trials (RCTs) and quasi-randomized trials, comparing continuous lateral rotation therapy (intervention) with conventional position changes (control). Risk of bias and quality of evidence for RCTs were assessed using the Cochrane Collaboration and Grading of Recommendations Assessment, Development, and Evaluation tools. For the quasi-randomized trials, the Risk of Bias in Non-Randomized Studies-of Interventions tool was used. RESULTS: In 18 studies with 1,466 participants (intervention, n = 700, 47.7%; control, n = 766, 52.2%), continuous lateral rotation therapy was predominantly used for prophylactic purposes, with protocols varying from 10-24 h/d. Meta-analysis (16 RCTs) favored continuous lateral rotation therapy for reduced mechanical ventilation duration (standardized mean difference [SMD] -0.17 [CI -0.29 to -0.04] d, P = .008) and lower nosocomial pneumonia incidence (odds ratio 0.39 [CI 0.29-0.52], P < .001). Continuous lateral rotation therapy showed no significant impact on mortality (odds ratio 1.04 [CI 0.80-1.34], P = .77), ICU LOS (SMD -0.11 [CI -0.25 to 0.02] d, P = .11), hospital LOS (SMD -0.10 [CI -0.31 to 0.11] d, P = .33), and incidence of pressure ulcers (odds ratio 0.73 [CI 0.34-1.60], P = .44). CONCLUSIONS: Continuous lateral rotation therapy showed no significant difference in primary outcomes (mortality, ICU and hospital LOS) but revealed significant differences in secondary outcomes (consistently reduced nosocomial pneumonia, with a minor effect on mechanical ventilation duration), supported by moderate certainty. Very low certainty for other outcomes highlights the need for current studies in diverse clinical settings and protocols to assess continuous lateral rotation therapy effectiveness.